2015
DOI: 10.1016/j.jevs.2014.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Equine Bone Marrow and Adipose Tissue Mesenchymal Stem Cells: Cytofluorimetric Characterization, In Vitro Differentiation, and Clinical Application

Abstract: a b s t r a c tThe aim of the present work was to isolate, cultivate, differentiate, and conduct cellular characterization of mesenchymal stem cells (MSCs) derived from equine adipose tissue (eAT) and bone marrow (eBM). Isolated and characterized cells were used in racehorses suffering from a superficial flexor tendon injury. Equine adipose tissue collection was performed at the base of the horse tail, whereas eBM was aspirated from iliac crest. Mononuclear cell fraction was isolated and cultured. In vitro dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Analysis of surface marker expression patterns provided further insights into the characteristics of human MSCs, but only one antibody of the panel available was cross-reacting with equine epitopes. This study confirms what already observed by others in the horse (9,10,29), and adds to the list a new antibody that does not recognize the corresponding equine epitope (CD 19, clone LT-19).…”
Section: Discussionsupporting
confidence: 90%
“…Analysis of surface marker expression patterns provided further insights into the characteristics of human MSCs, but only one antibody of the panel available was cross-reacting with equine epitopes. This study confirms what already observed by others in the horse (9,10,29), and adds to the list a new antibody that does not recognize the corresponding equine epitope (CD 19, clone LT-19).…”
Section: Discussionsupporting
confidence: 90%
“…All of our results showed that these cells have the capacity to synthesize a specific protein representative of hyaline articular cartilage in collagen sponges in the presence of chondrogenic factors. The comparison with other studies is not straightforward because other protocols perform chondrocyte differentiation in monolayer cultures [ 52 ], in pellet cultures [ 50 ], or in hydrogels [ 53 ] in the presence of only one growth factor. Equine MSCs derived from adipose tissue cultured in a micromass system at P4 showed only a non-significant induction of type II collagen and aggrecan [ 50 ] and at P2, Alcian blue staining was more intense at the periphery of cell pellets, giving evidence of an incomplete and heterogenous differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow (BM) is the common source of autologous MSCs for clinical applications in equine medicine. Alternatively, adipose tissue-derived MSCs can be used as they have a higher proliferation potential (Iacono et al 2015a). However, for both sources, an invasive procedure is required and a large variability in the cell yield related to the donor was demonstrated (Colleoni et al 2009).…”
Section: Introductionmentioning
confidence: 99%